Effect of Modified Duodenal Exclusion Surgery on Glucose Metabolism in Rats with Type 2 Diabetes Mellitus - YANG Jin; YU Shiya; LIN Nan; FANG Yongchao; ZHAO Hu; QIU Jinwei; LIN Hongming; CHEN Huiyan; WANG Yu; WU Weihang (Shiyan dongwu yu bijiao yixue)
Objective To investigate the impact of anti-reflux modified duodenal exclusion surgery on glucose metabolism in rats with type 2 diabetes mellitus (T2DM), and to elucidate the role of the duodenum in maintaining glucose homeostasis.MethodsForty male Sprague-Dawley rats aged 5 weeks were fed a high-fat diet and induced with T2DM using low-dose streptozotocin. Thirty-six rats that met the T2DM model criteria were randomly divided into three groups: the simple duodenal exclusion surgery group (DE group), the anti-reflux modified duodenal exclusion group (MDE group), and the sham operation group (SO group), with 12 rats in each group. Gastroenterography was performed 4 weeks after surgery, and the body weight, fasting blood glucose levels, and serum glucagon-like peptide-1 (GLP-1) concentrations were measured before surgery and at 1, 2, 4, and 8 weeks post-surgery. Eight weeks post-surgery, the rats were euthanized, and a 1 cm segment of the biliopancreatic loop was collected from each group for pathological sectioning and HE staining to observe the intestinal mucosal villus length under an optical microscope. Results Gastroenterography showed that there was significant reflux of the contrast agent into the duodenal lumen in the DE group, while no reflux was observed in the MDE group. At one week post-surgery, the body weights of rats in all three groups significantly decreased compared to before surgery (P<0.05), and then the body weights of all groups increased over time, with no significant differences between the groups (P>0.05). Compared with the SO group, the fasting blood glucose levels in the MDE and DE groups significantly decreased at all time points post-surgery (P<0.05), while GLP-1 concentrations significantly increased (P<0.05). The fasting blood glucose levels in the MDE group were lower than those in the DE group at all time points post-surgery (P<0.05), but there were no significant differences in serum GLP-1 concentrations between the MDE and DE groups (P>0.05). Regarding intestinal mucosal morphology, the villus lengths of the biliopancreatic loops in the MDE group were significantly shorter than those in the DE and SO groups (P<0.05). Conclusion Anti-reflux modified duodenal exclusion surgery effectively improves glucose metabolism in T2DM rats by preventing the reflux of chyme into the diverted duodenum, thereby enhancing its hypoglycemic effect.